Characteristics of respiratory viruses’ circulation through a six-year period (2016–2022) in a pediatric population in Normandy, France, and the impact of COVID-19 pandemic - J. Dina; A. Moisan; P. Thibon; C. Creveuil; J. Adnet; A. Vabret; J. Brouard; J. C. Plantier (Microbiology Spectrum, 2023)
ABSTRACT The impact of COVID-19 on the circulation of respiratory viruses has highlighted the need for ongoing surveillance and preparedness for emerging infectious diseases. The aim of this study was to provide information on the dynamics of respiratory viruses in pediatric populations to inform public health policies and strategies for the prevention and control of respiratory infections. This study analyzed data on the detection of respiratory viruses in pediatric populations from 2016 to 2022. The weekly number of tests and positive results for respiratory viruses were collected and analyzed from the two major university hospitals, Caen and Rouen. Different assays, including multiplex panels and rapid detection kits, were used for testing. The study analyzed the epidemiological trends of respiratory viruses in a French region during the COVID-19 pandemic. The data set included 37,969 tests, with a significant increase in the number of tests in 2020–2021 and 2021–2022. The rate of positive tests fell below 50% in 2021–2022. Enteroviruses (EV)/rhinoviruses (RV) and respiratory syncytial viruses (RSV) were the most frequently identified viruses, except in 2021–2022, when Flu ranked second. The Flu epidemic appeared slightly earlier in 2021–2022 and lasted for 25 weeks, with a doubling time of 4.03. The RSV epidemic occurred earlier in 2021–2022 and had similar dynamics to pre-pandemic years. EV/RV continued to circulate throughout the lockdowns, while low numbers of other viruses were detected. Our results emphasize the importance of continuing active surveillance of respiratory virus circulation and the need for new recommendations for respiratory virus detection in pediatric patients. IMPORTANCE The report highlights an epidemiological change in the circulation of respiratory viruses in pediatric populations due to strategies adopted against COVID-19 pandemic. COVID-19 has resulted in a significant increase in requests for multiplex respiratory research to identify the virus responsible for the symptoms. The diagnostic needs have increased, and the number of samples analyzed in 2021–2022 is equal to the samples analyzed over the four epidemic periods preceding the pandemic. The report suggests the importance of active surveillance of respiratory viruses' circulation and new recommendations for respiratory virus detection in pediatric patients.